2021
DOI: 10.1093/workar/waab002
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Age Differences in the Motivating Potential of Intergenerational Contact at Work

Abstract: Understanding the effects of intergenerational contact at work is important given aging and increasingly age-diverse workforces. The aim of this research was to better understand who derives motivational benefits from intergenerational contact, and the processes by which this occurs. To do so, we adopted a motivational lens grounded in need-based theories of work motivation and lifespan development theory. We argue that the motivating effect of intergenerational contact on work engagement via sense of belongin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 131 publications
0
13
0
2
Order By: Relevance
“…For example, age‐sensitive HR practices, such as flexible work arrangements and exemption from overtime (Allen et al, 2021; Shao et al., 2021), may be particularly promising in satisfying the needs of older workers and assuring their ability to attend and perform work. Moreover, in light of the age‐associated health decline and motivational benefits, promoting an age‐inclusive climate (Boehm et al., 2021; Li et al., 2021; Rudolph & Zacher, 2021) and promoting inter‐generational work collaboration (Burmeister et al., 2020, 2021) may leverage the advantages of employees at all ages.…”
Section: Discussionmentioning
confidence: 99%
“…For example, age‐sensitive HR practices, such as flexible work arrangements and exemption from overtime (Allen et al, 2021; Shao et al., 2021), may be particularly promising in satisfying the needs of older workers and assuring their ability to attend and perform work. Moreover, in light of the age‐associated health decline and motivational benefits, promoting an age‐inclusive climate (Boehm et al., 2021; Li et al., 2021; Rudolph & Zacher, 2021) and promoting inter‐generational work collaboration (Burmeister et al., 2020, 2021) may leverage the advantages of employees at all ages.…”
Section: Discussionmentioning
confidence: 99%
“…De Lange et al ( 2010 ), Kooij et al ( 2013a ), and Burmeister et al ( 2021 ) found that generativity is positively related to work engagement. Employees feel more connected and closer to each other due to the unique nature of intergenerational contact (Burmeister et al 2021 ).…”
Section: Generativity and Individual Outcomesmentioning
confidence: 99%
“…De Lange et al ( 2010 ), Kooij et al ( 2013a ), and Burmeister et al ( 2021 ) found that generativity is positively related to work engagement. Employees feel more connected and closer to each other due to the unique nature of intergenerational contact (Burmeister et al 2021 ). As Ding and Schuett ( 2020 ) found generativity also has a positive effect on volunteers—the higher the generativity level, the higher their motivations, satisfaction, and commitment.…”
Section: Generativity and Individual Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, when an older employee experiences positive interactions with younger colleagues at work, this makes the former's job more interesting and enjoyable. In contrast to negative relationships at work, which prompt an avoidance reaction that discourages individuals from searching for new information (Yang & Kahlor, 2013), positive relationships prompt an approach reaction that fosters the exploration of new development opportunities and makes older employees less concerned about performance deficiencies and more engaged at and with their work (Abrams, Eller, & Bryant, 2006; Burmeister, Hirschi, et al, 2021). To summarise, we propose that age‐inclusive HR practices improve older employees' contact quality with their younger colleagues, which, in turn, increases the former's motivation to expand their knowledge and skills at work:Hypothesis Age‐inclusive HR practices have a positive indirect relation with older employees' development striving via their contact quality with younger colleagues.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%